Epigenetic Regulatory Mechanisms Associated with Infertility - Sheroy Minocherhomji; Prochi F. Madon; Firuza R. Parikh (Obstetrics and Gynecology International)
Infertility is a complex human condition and is known to be caused by numerous factors including genetic alterations and abnormalities. Increasing evidence from studies has associated perturbed epigenetic mechanisms with spermatogenesis and infertility. However, there has been no consensus on whether one or a collective of these altered states is responsible for the onset of infertility. Epigenetic alterations involve changes in factors that regulate gene expression without altering the physical sequence of DNA. Understanding these altered epigenetic states at the genomic level along with higher order organisation of chromatin in genes associated with infertility and pericentromeric regions of chromosomes, particularly 9 and Y, could further identify causes of idiopathic infertility. Determining the association between DNA methylation, chromatin state, and noncoding RNAs with the phenotype could further determine what possible mechanisms are involved. This paper reviews certain mechanisms of epigenetic regulation with particular emphasis on their possible role in infertility.